The role of leadership in sustainable digital transformation of the organization - Dharmendra Hariyani; Poonam Hariyani; Sanjeev Mishra (Sustainable Futures)
Digital transformation (DT) is a strategic imperative for organizations striving to remain competitive and adaptive in an evolving business environment. Leadership is central to achieving sustainable DT, as it drives innovation, resilience, and long-term strategic alignment. This review explores the role of leadership in the success of sustainable DT. A systematic review methodology was employed, using targeted keyword searches in the Scopus database. A total of 224 relevant articles, from 2011 to 2024, were included in the study based on the review objectives. The review reveals that transformational, adaptive, and ethical leadership styles are instrumental in driving sustainable DT by shaping an organizational culture, articulating a sustainability-aligned digital vision, and fostering stakeholder engagement. Key findings show that leadership significantly influences sustainable DT outcomes through six integrated mechanisms: strategic alignment, change management, talent empowerment, ecosystem collaboration, regulatory adaptation, and stakeholder value creation. Moreover, the study identifies persistent challenges such as legacy systems, skills gaps, and fragmented governance, and proposes evidence-based leadership strategies to overcome these barriers. The review also provides a synthesized framework that maps leadership roles to specific SDG targets, offering a practical lens for aligning digital initiatives with global sustainability objectives. This framework guides leadership development and policy design by clarifying how leadership integrates sustainability into DT initiatives, thereby advancing theoretical discourse and offering practical insights for fostering inclusive, responsible, and resilient DT.